Surface salt segregation polymer electrolyte as well as preparation method and application thereof
By utilizing the difference in boiling point of the solvent, solute salt enrichment is achieved, and the surface salt segregation polymer electrolyte is prepared, which solves the problems of low conductivity and mechanical strength of polymer solid electrolytes, and achieves efficient and stable operation and low-cost production of solid-state batteries.
Patent Information
- Application Number
- CN202411493423.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing polymer solid electrolytes have low room temperature ion conductivity, and high salt concentration leads to reduced mechanical strength and difficult processing, making it difficult to suppress the growth of metal negative electrode dendrites, resulting in battery short-circuit failure.
By utilizing the boiling points and volatile differences of different solvents, local enrichment of solute salts in high-boiling solvents is achieved. Combined with the traditional sol drying film formation method, surface salt segregation polymer electrolyte is prepared, with excellent ionic conductivity and mechanical properties .
It realizes long-term and stable operation of solid-state batteries, improves electrode interface stability and mechanical performance, reduces energy consumption and synthesis costs, and is suitable for industrial production.
Smart Images

Figure CN119315100A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of solid-state and semi-solid-state batteries, and specifically relates to surface salt segregation polymer electrolytes and preparation methods and applications thereof. Background Art
[0002] Most of the high-energy-density electrochemical energy storage systems currently under development, such as lithium-ion batteries, use organic liquid electrolytes, which have the advantages of good wettability and high ionic conductivity. However, in the pursuit of safer and higher-energy-density electrochemical energy storage systems, the solidification of electrolytes is the main trend in the future development of batteries. Solid electrolytes, as a bridge for ion transmission between positive and negative electrodes, are the core components of solid-state batteries, and their properties are key factors that significantly affect the reversible capacity, safety, and cycle life of all-solid-state batteries.
[0003] Among the many reported solid electrolytes, polymer electrolytes have attracted much attention due to their excellent ductility, close interface contact and simple manufacturing technology, and are considered to be one of the ideal solid electrolytes for the development of solid-state batteries. However, the low room temperature ionic conductivity severely limits its practical application. So far, most of the research on polymer electrolytes has been focused on optimizing the polymer skeleton structure, component types and ratios, and improving the complexation / dissociation rate of cations between segments or forming a fast ion transport network by regulating the polymer crystallinity, glass transition temperature and mesostructure, with the target electrolyte having a high composition uniformity; or focusing on constructing interlayer or mixed-phase structures, by simply superimposing and mixing multiple components with different polymer types or different filler concentrations, in order to achieve the purpose of balancing the overall electrochemical properties and mechanical strength of the electrolyte. When using this composite method, the ion migration barrier at the interface of different components is high, and chemical degradation or stress changes during battery charging and discharging can easily lead to two-phase peeling.
[0004] In fact, the decomposition of small molecule salts is an important source of components in the positive and negative electrode interface layers (CEI, SEI). Increasing the concentration of salts involved in the interfacial reaction is conducive to the formation of CEI / SEI membranes with high mechanical strength, high ion flux, and high electrochemical stability, ensuring the efficient operation of the battery. Similar high-concentration salt systems such as "salt-in-polymer" have been reported. Excessive overall salt concentration will lead to reduced mechanical strength and increased viscosity of the electrolyte. While the electrolyte and electrode are in closer contact, it also increases the difficulty of battery processing. During battery operation, the growth of dendrites of the metal negative electrode (such as metallic lithium and sodium) is difficult to inhibit, which in turn induces short-circuit failure of the battery. Therefore, it is particularly important to study the thermodynamic and kinetic behavior of the distribution of solute salts during the casting process of polymer solid electrolytes and to achieve continuous concentration distribution of solute salts at their surface interfaces and bulk phases. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a surface salt segregation polymer electrolyte and a preparation method thereof and application in solid-state batteries and semi-solid-state batteries. The present invention utilizes the boiling point, volatility, and solubility difference of different solvents to polymers and solute salts. During the film-forming process, due to the differences in the physical and chemical properties of different solvents, as the gradient volatilization of the solvent occurs, the solute salt is locally enriched in the high-boiling-point solvent. The dried product has the characteristics of surface salt segregation. The traditional sol drying film-forming method is combined to obtain the preparation method of the surface salt segregation polymer electrolyte of the present invention. The preparation method of the present invention has the characteristics of low energy consumption and easy processing. Assembling the solid electrolyte into a solid-state battery can achieve long-term and stable operation of the battery.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] In a first aspect, the present invention provides a surface salt segregation polymer electrolyte, wherein the polymer electrolyte has the characteristics of surface salt segregation and has both excellent ionic conductivity and mechanical properties.
[0008] In a second aspect, the present invention provides a method for preparing a surface salt segregation polymer electrolyte, comprising the following steps:
[0009] S1: adding a mixed solvent consisting of a low boiling point, high polymer solubility solvent and a high boiling point, high salt solubility, low polymer solubility solvent to the high molecular skeleton polymer, solute salt and / or filler powder, and mixing all the components uniformly by stirring, homogenizing, or ball milling to obtain a target casting solution;
[0010] S2: casting the casting solution obtained in step S1 into a film, or casting, coating or applying it on a porous support membrane;
[0011] S3: Drying the film obtained in step S2 to obtain a polymer electrolyte.
[0012] Based on the above technical solution, further, in step S1, the mass ratio of the high molecular skeleton polymer, the solute salt and the filler powder is (0.2-20):1:(0-1), preferably (0.5-4):1:(0-0.5).
[0013] Based on the above technical scheme, further, the high molecular skeleton polymer described in step S1 includes but is not limited to polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyvinylidene fluoride-trifluoroethylene (PVDF-TrFE), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polysulfone, polyphenylene ether, polyether, polyester, rubber elastomer, fluoropolyester, fluororubber elastomer, fluoropolysulfone, fluoropolyphenylene ether, fluoropolyether, fluoropolyester, fluororubber elastomer, etc. One or more combinations of two or more.
[0014] Based on the above technical solution, further, the cations in the solute salt described in step S1 include but are not limited to lithium ions (Li + ), sodium ion (Na + ) or potassium ion (K + ), anions include but are not limited to bis(trifluoromethanesulfonyl)imide (TFSI - ), bis(fluorosulfonyl)imide (FSI - ), trifluoromethanesulfonyl (OTf-), perchlorate (ClO4 - ), tetrafluoroborate (BF4 - ), hexafluorophosphate (PF6 - ), hexafluoroarsenate (AsF6 - ), nitrate (NO3 - ), bis(oxalatoborate) (BOB - ), difluorooxalate boric acid (ODFB - ) or a combination of two or more thereof.
[0015] Based on the above technical solution, further, the filler powder described in step S1 includes but is not limited to one or a combination of two or more of inorganic solid electrolytes, metal organic framework compounds (MOFs) or other ion transport inert materials.
[0016] Based on the above technical solution, further, the filler powder described in step S1 is preferably Na3Zr2Si2PO 12 , Li 6.25 Al 0.25 La3Zr2O 12 .
[0017] Based on the above technical solution, further, the boiling point difference between the low boiling point solvent and the high boiling point solvent in step S1 is higher than 5°C, preferably ≥50°C; the volume ratio of the low boiling point solvent to the high boiling point solvent is (0.5~1000):1, preferably (1~100):1.
[0018] Based on the above technical scheme, further, the low boiling point solvent in step S1 includes but is not limited to methanol, ethanol, propanol, N,N-dimethylformamide, butyronitrile, acetone, tetrahydrofuran, etc., and the high boiling point solvent includes but is not limited to propylene carbonate, triethyl fluorophosphate (FTEP), fluoroethylene carbonate (FEC) or trifluoromethylethylene carbonate (TFEC), etc.
[0019] Based on the above technical solution, further, the solid content of the casting solution in step S1 is 5 to 90 wt %.
[0020] Based on the above technical solution, further, the porosity of the porous support membrane described in step S2 is 10-98%, and the body material is polyethylene (PE), polypropylene (PP), polyimide (PI) or a composite polymer material.
[0021] Based on the above technical solution, further, in step S3, the drying time is 10 minutes to 72 hours, and a step-by-step drying program can be set.
[0022] In a third aspect, the present invention provides the above-mentioned surface salt segregation polymer electrolyte, and the surface salt segregation polymer electrolyte prepared by the above-mentioned preparation method for use in solid-state batteries and semi-solid-state battery systems.
[0023] Based on the above technical solution, it further includes primary batteries, secondary batteries, ion batteries, metal batteries, etc.
[0024] Based on the above technical solution, further, the solid-state battery and semi-solid-state battery are used in portable electronic products, or in transportation equipment such as electric vehicles and drones, or in large-scale energy storage power stations.
[0025] The preparation method of the present invention and the obtained product have the following advantages and beneficial effects:
[0026] (1) The present invention utilizes the differences in the physical and chemical properties of different solvents to achieve the enrichment of small molecule salts on the surface of the polymer electrolyte through a simple surface salt segregation process, thereby forming CEI and SEI layers rich in inorganic components on the electrode surface, thereby improving the interface stability of the solid electrolyte-electrode.
[0027] (2) The salt-enriched surface achieved by the surface polymer electrolyte salt segregation method proposed in the present invention is a dense membrane structure. The composition changes continuously from the surface to the bulk phase, and it is not easy to produce holes or phase separation. While forming a close and stable interfacial contact, it retains the excellent mechanical properties of the low-solvent, low-salt content bulk electrolyte. The prepared solid-state battery has excellent overall performance.
[0028] (3) The method for surface salt segregation of polymer electrolytes proposed in the present invention is simple to operate, has low synthesis cost, low energy consumption, and is environmentally friendly. It is suitable for practical application in solid-state batteries and is conducive to industrial-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention, the drawings related to the embodiments are briefly introduced below.
[0030] Figure 1 It is a schematic diagram of the production of the surface salt segregation polymer electrolyte membrane of the present invention.
[0031] Figure 2 The time-of-flight secondary ion mass spectrometry test of the surface salt segregation polymer electrolyte membrane obtained in Example 1 is CF3SO2 - 3D rendering of .
[0032] Figure 3 Time-of-flight secondary ion mass spectrometry test of the surface salt segregation polymer electrolyte membrane obtained in Comparative Example 1 CF3SO2 - 3D rendering of .
[0033] Figure 4 This is a scanning probe microscope image of the surface salt segregation polymer electrolyte membrane obtained in Example 1. The particles in the image are inorganic fillers.
[0034] Figure 5 This is a graph showing the change in ionic conductivity of the surface salt segregation polymer electrolyte membrane obtained in Example 1 with temperature.
[0035] Figure 6 The sodium / sodium symmetric battery assembled using the surface salt segregation polymer membrane obtained in Example 1 was tested at 0.5 mA cm -2 Current density, 0.5 mAh cm -2 Sodium stripping / deposition cycle curve at the surface capacity.
[0036] Figure 7 The sodium / sodium symmetric battery assembled using the surface salt segregation polymer membrane obtained in Example 1 was -2 Current density, 1mAh cm -2 Sodium stripping / deposition cycle curve at the surface capacity.
[0037] Figure 8 This is a rate performance diagram of a sodium iron pyrophosphate / sodium solid-state battery assembled using the surface salt segregation polymer membrane obtained in Example 1 of the present invention.
[0038] Fig. 9 This is a cycling performance diagram of a Na / sodium iron pyrophosphate solid-state battery assembled using the surface salt segregation polymer membrane obtained in Example 1 at a current density of 1C. DETAILED DESCRIPTION
[0039] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0040] Example 1
[0041] This embodiment provides a method for preparing a surface salt segregation polymer electrolyte membrane, comprising the following steps:
[0042] (1) Dissolve 0.5 g of polyvinylidene fluoride (PVDF) powder and 0.352 g of sodium bis(fluorosulfonyl)imide (NaFSI) in 6 mL of anhydrous N,N-dimethylformamide (DMF), stir at 60 °C for 1 h to dissolve, and add 0.1 g of Na3Zr2Si2PO 12 Nanopowder (purchased from Shenzhen Kejing Zhida Technology Co., Ltd.) was stirred continuously at room temperature for 3 h until the nanoparticles were evenly dispersed in the solution;
[0043] (2) adding 0.65 mL of trifluoromethylethylene carbonate (TFEC) solvent to the dispersion obtained in step (1) above, and continuing stirring for 1 h until all components are evenly mixed;
[0044] (3) The casting mixture obtained in step (2) was cast into a film in an argon atmosphere glove box, transferred to a vacuum drying oven, and vacuum dried at 65° C. for 24 h. After drying, the obtained film thickness was 40 μm, and the film was cut into a circular polymer electrolyte membrane with a diameter of 19 mm in the glove box.
[0045] Time-of-flight secondary ion mass spectrometry test of the surface salt segregation polymer electrolyte membrane obtained in Example 1 CF3SO2 - A 3D rendering of Figure 2 As shown in the figure, CF3SO2 - For FSI - Mass spectrometry dissociation products, the color depth in the figure represents CF3SO2 - The higher the concentration, the darker the surface rendering means that NaFSI is enriched on the surface of the material membrane. The scanning probe microscope image of the surface salt segregation polymer electrolyte membrane obtained in Example 1 is as follows: Figure 4 As shown, Figure 2 and Figure 4 The results show that the polymer electrolyte membrane obtained in Example 1 has surface NaFSI salt segregation and a dense membrane structure.
[0046] Example 2
[0047] This embodiment provides a method for preparing a surface salt segregation polymer electrolyte membrane, comprising the following steps:
[0048] (1) Dissolve 0.5 g PVDF powder and 0.352 g NaFSI in 6 mL of anhydrous N,N-dimethylformamide (DMF), stir at 60 °C for 1 h to dissolve, and add 0.1 g Na3Zr2Si2PO 12 Nanopowder was stirred continuously at room temperature for 3 h until the nanoparticles were evenly dispersed in the solution;
[0049] (2) adding 0.65 mL of trifluoromethylethylene carbonate (TFEC) solvent to the dispersion obtained in step (1) above, and continuing stirring for 1 h until all components are evenly mixed;
[0050] (3) In an argon atmosphere glove box, the casting mixture obtained in step (2) was coated on a porous polypropylene (PP) diaphragm with a porosity of 70% (pore size of about 1 micron, thickness of about 10 microns), and after drying, the other side was coated (coating process was the same as above), and vacuum dried at 65° C. for 24 hours. After drying, the membrane thickness was 35 microns, and it was cut into a circular polymer electrolyte membrane with a diameter of 19 mm.
[0051] Example 3
[0052] This embodiment provides a method for preparing a surface salt segregation polymer electrolyte membrane, comprising the following steps:
[0053] (1) 0.5 g of polyethylene oxide (PEO) powder and 0.352 g of NaFSI were dissolved in 6 mL of anhydrous butyronitrile and ball-milled at 300 rpm for 2 h. 0.1 g of Na3Zr2Si2PO4 was added. 12 Nanopowder, continue ball milling for 3 h until a uniform dispersed solution is obtained;
[0054] (2) adding 0.65 mL of triethyl fluorophosphate (FTEP) solvent to the dispersion obtained in step (1) above, and continuing ball milling for 1 h until all components are evenly mixed;
[0055] (3) The casting mixture obtained in step (2) was cast into a film in an argon atmosphere glove box, transferred to a vacuum drying oven, and vacuum dried at 65° C. for 30 h. The film thickness after drying was 45 μm, and was cut into a circular polymer electrolyte membrane with a diameter of 19 mm in the glove box.
[0056] Example 4
[0057] This embodiment provides a method for preparing a surface salt segregation polymer electrolyte membrane, comprising the following steps:
[0058] (1) 0.5 g of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) powder and 0.4 g of lithium bis(fluorosulfonyl)imide (LiFSI) were dissolved in 6 mL of anhydrous DMF and stirred at 60 °C for 1 h to dissolve. 0.1 g of LLZTO (Li 6.25 Al 0.25 La3Zr2O 12 , purchased from Ronggu New Material Technology (Shaoxing) Co., Ltd.) nanopowder and 0.65 mL of trifluoromethylethylene carbonate (TFEC) solvent, and stirring was continued for 3 h until the inorganic nanoparticles were uniformly dispersed in the solution.
[0059] (2) The casting mixture obtained in step (1) was cast into a film in an argon atmosphere glove box, transferred to a vacuum drying oven, and vacuum dried at 65° C. for 30 h. The film thickness after drying was 43 μm, and was cut into a circular polymer electrolyte membrane with a diameter of 19 mm in the glove box.
[0060] Example 5
[0061] This embodiment provides a method for preparing a surface salt segregation polymer electrolyte membrane, comprising the following steps:
[0062] (1) 0.5 g PVDF-HFP powder and 0.4 g LiFSI were dissolved in 6 mL of anhydrous DMF and stirred at 60 °C for 1 h to dissolve. 0.1 g LLZTO nanopowder and 0.65 mL of triethyl fluorophosphate (FTEP) solvent were added and stirred for 3 h until the inorganic nanoparticles were uniformly dispersed in the solution.
[0063] (2) The cast film mixture obtained in step (1) was coated on a porous polyimide (PI, pore size of about 2 μm, thickness of 10 μm) diaphragm with a porosity of 70%, and after drying, the other side was coated (the coating process was the same as above), and vacuum dried at 65° C. for 30 h. After drying, the film thickness was 30 μm, and it was cut into a circular polymer electrolyte membrane with a diameter of 19 mm in a glove box.
[0064] Comparative Example 1
[0065] This embodiment provides a method for preparing a polymer electrolyte membrane, comprising the following steps:
[0066] (1) Dissolve 0.5 g PVDF powder and 0.352 g NaFSI in 6 mL of anhydrous N,N-dimethylformamide (DMF), stir at 60 °C for 1 h to dissolve, and add 0.1 g Na3Zr2Si2PO 12 Nanopowder was stirred continuously at room temperature for 3 h until the nanoparticles were evenly dispersed in the solution;
[0067] (2) The casting mixture obtained in step (1) was cast into a film in an argon atmosphere glove box, transferred to a vacuum drying oven, and vacuum dried at 65° C. for 24 hours. The film thickness after drying was 40 μm, and was cut into a circular polymer electrolyte membrane with a diameter of 19 mm in the glove box.
[0068] Time-of-flight secondary ion mass spectrometry test of the surface salt segregation polymer electrolyte membrane obtained in Comparative Example 1 CF3SO2 - A 3D rendering of Figure 3 As shown, no regular distribution of color depth was observed in the figure, and the results showed that NaFSI was not enriched on the surface of the polymer electrolyte membrane obtained in Comparative Example 1.
[0069] Example 6
[0070] This embodiment provides a method for assembling and testing a solid-state battery containing a polymer electrolyte membrane, and the specific process steps are as follows:
[0071] 1. The ionic conductivity of the polymer electrolyte was measured by the AC impedance of the assembled half-cell. The room temperature ionic conductivity of the surface salt segregation polymer electrolyte prepared in Example 1 was 0.56 mS cm -1 ,like Figure 5 shown.
[0072] 2. Assemble sodium / sodium symmetric batteries, with sodium metal as the positive and negative electrodes and polymer electrolyte as the separator, in a glove box. The assembled sodium / sodium symmetric battery was tested for current cycling performance at room temperature. The sodium / sodium symmetric battery assembled with the surface salt segregation polymer electrolyte membrane prepared in Example 1 had a current cycling performance of 0.5 mA cm -2 or 1mA cm -2 The current cycling performance is as follows Figure 6 and Figure 7 As shown in the figure, the cycling performance remains relatively stable after 700 h and 350 h of cycling, and the polarization voltage is about 0.2 V.
[0073] 3. Assemble a solid-state sodium battery (sodium iron phosphate pyrophosphate / sodium battery), the positive electrode is sodium iron phosphate pyrophosphate, and the negative electrode is sodium metal. The assembled solid-state sodium battery is tested for charge and discharge performance at 25°C. The rate performance of the solid-state sodium battery assembled with the surface salt segregation polymer electrolyte prepared in Example 1 is as follows Figure 8 As shown, at 0.2C, 0.5C, 1C, 2C, 4C, 6C, 8C (1C = 129mA g -1 ) are 112 mAh g -1 , 105mAh g -1 , 100mAh g -1 , 95mAh g -1 , 90mAh g -1, 73mAh g -1 , 40mAh g -1 .
[0074] The cycle performance of the solid-state sodium battery assembled with the surface salt segregation polymer electrolyte prepared in Example 1 is as follows Fig. 9 As shown, 1C (1C = 129mAg -1 ) The discharge capacity is about 103 mAh g -1 , the capacity retention rate after 750 cycles is 97.5%.
[0075] Table 1 Properties of polymer electrolytes prepared in Examples 1-5 and Comparative Example 1 and their electrochemical properties in all-solid-state sodium batteries
[0076] High boiling point solvent Porous support membrane Tensile modulus Room temperature ionic conductivity 1C*500 cycles capacity retention rate Example 1 TFEC none 6.3MPa <![CDATA[5.6×10 -4 S cm -1 ]]> 92.0% Example 2 TFEC PP 60MPa <![CDATA[6.7×10 -4 S cm -1 ]]> 98.5% Example 3 FTEP none 10.1MPa <![CDATA[4.2×10 -4 S cm -1 ]]> 88.1% Example 4 TFEC none 7.6MPa <![CDATA[3.1×10 -4 S cm -1 ]]> 84.5% Example 5 FTEP PI 100.2MPa <![CDATA[6.2×10 -4 S cm -1 ]]> 96.6% Comparative Example 1 none none 0.5MPa <![CDATA[1.2×10 -4 S cm -1 ]]> 5.2%
[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A surface salt segregation polymer electrolyte, characterized in that: The surface of the polymer electrolyte is enriched with salt.
2. A method for preparing a surface salt segregation polymer electrolyte, characterized in that: The steps include: S1: adding a mixed solvent consisting of a low boiling point, high polymer solubility solvent and a high boiling point, high salt solubility, low polymer solubility solvent to the high molecular skeleton polymer, solute salt and / or filler powder, and mixing all the components uniformly by stirring, homogenizing, or ball milling to obtain a target casting solution; S2: casting the casting solution obtained in step S1 into a film, or casting, coating or applying it on a porous support membrane; S3: Drying the film obtained in step S2 to obtain a polymer electrolyte.
3. The preparation method according to claim 2, characterized in that: The mass ratio of the high molecular skeleton polymer, the solute salt and the filler powder in step S1 is (0.2-20):1:(0-1), preferably (0.5-4):1:(0-0.5).
4. The preparation method according to claim 2, characterized in that: The macromolecular skeleton polymer described in step S1 includes but is not limited to one or a combination of two or more of poly(ethylene oxide) (PEO), poly(vinylidene fluoride) (PVDF), poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP), poly(vinylidene fluoride-trifluoroethylene) (PVDF-TrFE), polyacrylonitrile (PAN), poly(methyl methacrylate) (PMMA), polysulfone, polyphenylene ether, polyether, polyester, rubber elastomer, fluoropolyester, fluororubber elastomer, fluoropolysulfone, fluoropolyphenylene ether, fluoropolyether, fluoropolyester, fluororubber elastomer, etc.; The cations in the solute salt include but are not limited to lithium ions (Li + ), sodium ion (Na + ) or potassium ion (K + ), anions include but are not limited to bis(trifluoromethanesulfonyl)imide (TFSI - ), bis(fluorosulfonyl)imide (FSI - ), trifluoromethanesulfonyl (OTf-), perchlorate (ClO4 - ), tetrafluoroborate (BF4 - ), hexafluorophosphate (PF6 - ), hexafluoroarsenate (AsF6 - ), nitrate (NO3 - ), bis(oxalatoborate) (BOB - ), difluorooxalate boric acid (ODFB - ) or a combination of two or more thereof; The filler powder includes but is not limited to inorganic solid electrolytes, metal organic framework compounds (MOFs) or other ion transport inert materials, one or a combination of two or more, preferably Na3Zr2Si2PO 12 , Li 6.25 Al 0.25 La3Zr2O 12 .
5. The preparation method according to claim 2, characterized in that: In step S1, the boiling point difference between the low boiling point solvent and the high boiling point solvent is higher than 5°C, preferably ≥50°C; the volume ratio of the low boiling point solvent to the high boiling point solvent is (0.5-1000):1, preferably (1-100):
1.
6. The preparation method according to claim 5, characterized in that: The low boiling point solvent in step S1 includes but is not limited to methanol, ethanol, propanol, N,N-dimethylformamide, butyronitrile, acetone, tetrahydrofuran, etc., and the high boiling point solvent includes but is not limited to propylene carbonate, triethyl fluorophosphate (FTEP), fluoroethylene carbonate (FEC), trifluoromethylethylene carbonate (TFEC), etc.
7. The preparation method according to claim 2, characterized in that: The solid content of the casting solution in step S1 is 5 to 90 wt %.
8. The preparation method according to claim 2, characterized in that: The porosity of the porous support membrane is 10-98%, and the specific material is polyethylene (PE), polypropylene (PP), polyimide (PI) or composite polymer material.
9. The surface salt segregation polymer electrolyte according to claim 1 and the surface salt segregation polymer electrolyte prepared by the preparation method according to any one of claims 2 to 8 are used in solid-state batteries and semi-solid-state battery systems.
Citation Information
Patent Citations
Preparation method, product and application of single-phase compact polymer electrolyte
CN113517469A
Preparation method of polyvinylidene fluoride-hexafluoropropylene copolymer composite electrolyte diaphragm
CN117578027A
Lithium metal battery fluorine-containing polymer solid electrolyte working at room temperature
CN117954681A
Solid-state electrochemical cells, processes for their preparation and uses thereof
US20230136818A1